Does television viewing make children obese? a review - Nuru, Hasanuddin; Piaseu, Noppawan; Palutturi, Sukri; R, Rasdin; Z, Zaenal; Mustamin, Rini; Mamang, Fardiana (International Journal of Research in Medical Sciences, 2016)
Watching television (TV) is an activity that very common and increasing in children and will lead to the adverse effects on health. This study aim to inform the readers, how TV viewing influences of weighs gain in the children. This data was collected from January 2003 to 2013 used Google scholar and PubMed databases with the published papers only. The articles were limited to English language and focus on the TV viewing, obesity and children as keywords. TV viewing has great influence to the consumption of high-fat foods whereas increase body mass index (BMI) eventually. Those who watch more frequently commercial TV will stimulates food intake and overconsumption, it’s also promote sedentary behavior, less energy expenditure and have high risk to be obesity. TV viewing not just promote sedentary behavior or less energy expenditure but also stimulates food intake, overconsumption, influence food choice and eating occasion in front of the screen, whereas have significant correlation to the obesity in children.